The Seroepidemiological Studies of Sand fly fever in Iran During Imposed War - A Mehrabi Tavana (Tehran University of Medical Sciences, 2001)
Little is known about sand fly fever with manifestations such as severe fever, headache and photophobia at the frontiers before the imposed war Iraq against Iran (1980-1988). In this article the seroepidemiological study of sand fly fever in different western provinces of Iran were investigated during imposed war Iraq against Iran from March 1987 to March 1988. Seroepidemiological studies were carried out on affected soldiers by using Complement fixation (CF) and Hemmglutination inhibition (HI) tests. Two serums were taken, first in the acute period and the second one in convalescence period of the disease. Obtained results showed that in mehran (Ilam) province 60% of combatants had antiserum against Sicilian and 46% had the Naples virus. In Gilaneghrab (Kermanshah province) all three sera obtained from three combatants were positive for Sicilian virus and one at them was positive for the Naples virus as well. The findings showed that, non-immure people travelling to the western boarders of Iran, are taken as susceptible to the disease. Consequently, should be protected appropriately protection including usage health measures in particular using bed-net and repellents